THE INFLUENCE OF GLOBALIZATION ON THE SPREAD OF ENGLISH AS A LINGUA FRANCA - Rasulova Diyora Ziyodulla qizi; Abduramanova Diana Valerevna (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2024)
Globalization has significantly contributed to the rise of English as a global lingua franca, reshaping communication, commerce, education, and cultural exchange across diverse regions. This article explores the multifaceted relationship between globalization and the widespread adoption of English, highlighting its role as a bridge language in multinational business, diplomacy, and digital connectivity. It examines how globalization has reinforced the dominance of English through global media, technological innovation, and international migration, while also analyzing its impact on local languages and cultural identities. The article further discusses the challenges posed by this linguistic shift, such as linguistic imperialism and the potential erosion of linguistic diversity, and considers emerging trends that may influence the future status of English in an increasingly interconnected world.